1961
DOI: 10.1152/jappl.1961.16.5.851
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short periods of arterial occlusion on blood flow and oxygen uptake

Abstract: In 17 experiments, performed on the forearm of normal subjects, the effect of 2½, 5, and 10 min of arterial occlusion was studied. Blood flow was obtained with the venous occlusion plethysmograph, and oxygen uptake was calculated using the Fick principle. Arterial occlusion resulted in the production of an oxygen debt which was subsequently repaid. With progressively longer periods of anoxia there was a proportionate increase in the magnitude of the debt. Similar conclusions could not be drawn from blood flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

1963
1963
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…The authors found the longer period of tissue hypoxia in the forearm to lead to increased duration of hyperemia as described above and the magnitude of the peak flow, which occurred within 10 – 15s, increased only marginally after a 5-minute occlusion compared to 3 minute. A direct comparison cannot be made between our data and the results of Nishiyama et al(29) and Abramson et al (30) because we are quantifying venous blood oxygenation instead of arterial blood flow rate. However, it is intuitive that the washout time and upslope – parameters that characterize the early phase of hyperemia - are most likely related to the magnitude and time required to achieve peak post-ischemic flow rate.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…The authors found the longer period of tissue hypoxia in the forearm to lead to increased duration of hyperemia as described above and the magnitude of the peak flow, which occurred within 10 – 15s, increased only marginally after a 5-minute occlusion compared to 3 minute. A direct comparison cannot be made between our data and the results of Nishiyama et al(29) and Abramson et al (30) because we are quantifying venous blood oxygenation instead of arterial blood flow rate. However, it is intuitive that the washout time and upslope – parameters that characterize the early phase of hyperemia - are most likely related to the magnitude and time required to achieve peak post-ischemic flow rate.…”
Section: Discussioncontrasting
confidence: 64%
“…Nishiyama et al (29) found the blood flow rate during the recovery period to be much greater in young healthy subjects and, according to the work by Abramson et al (30), is maintained longer in proportion to the cuff-occlusion period. Similarly, we found a greater overshoot in the younger compared to the older healthy age group, an effect that was significant for 5 minutes (p = 0.0116) but not for 3 minutes of occlusion (p < 0.16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that after five minutes of ischemia, controlled re-entry of blood at the preocclusion flow rate was enough to abolish reactive hyperemia, i. e., the "overshoot" was not necessary for repayment of debt. There are better studies which examine the total oxygen debt, and its subsequent repayment as was done in skeletal muscle by Abramson et al, 1 Yonce and Hamilton, 18 and Crawford et al, 84 and in the heart by Coffman and Gregg. 16 This has not been studied systematically in the intestine, but based upon available data from this laboratory, an estimate of re-…”
Section: Experiments In Which Warmed Unoxygenated Dextran Solution Wmentioning
confidence: 99%
“…The magnetic susceptibility of blood is determined by the volume fraction of the paramagnetic deoxyhemoglobin in red blood cells 39 and scales linearly with (1 – HbO2). Under normal conditions tissue oxygen debt created by periods of ischemia due to arterial occlusion is followed by reactive hyperemia and increased oxygen uptake 40 . As such, repeated measurements of venous oxygen saturation following a period of hypoxia reflect the rate at which deoxygenated blood is replaced, which depends on endothelial function.…”
Section: Susceptibility-weighted Magnetic Resonance Oximetrymentioning
confidence: 99%